214k views
0 votes
I need help with this problem and please show step by step

I need help with this problem and please show step by step-example-1

1 Answer

5 votes

Answer:

a).


{ \bf{first \: term}} \\ let \: n = 1 \\ n_(1) = {1}^(2) + 3(1) + 1 \\ n_(1) = 5 \\ \\ { \bf{second \: term}} \\ let \: n = 2 \\ n_(2) = {2}^(2) + 3(2) + 1 \\ n_(2) = 11 \\ \\ { \bf{third \: term}} \\ n_(3) = {3}^(2) + 3(3) + 1 \\ n_(3) = 19 \\ \\ { \bf{fourth \: term}} \\ n_(4) = {4}^(2) + 3(4) + 1 \\ n_(4) = 29

b).

common difference, d:


d = n_(4) - n_(3) \\ d = 29 - 19 \\ d = 10\\ but \: increases \: by \: 2 \\ d = 10 + 2 = 12\\ therefore : \\ n_(5) = n_(4) + d \\ n_(5) = 29 + 12 \\ n_(5) = 41

c).


n_(5) = {5}^(2) + 3(5) + 1 \\ n_(5) = 41

yes it is the same

User Carlos Cardenas
by
5.0k points